IMPLEMENTATION OF OPERANT CONDITIONING THEORY FOR HABITUATION OF STUDENTS IN WORSHIP AT SMPIT RABBI RADHIYYA CURUP - Sutarto Sutarto (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
Recently, many Islamic schools have special programs to bias students in voting, but they do not yet have the right formula for implementing the plan. This study examines the implementation of operational conditioning to form students in theory at the Rabbi Radhiyya Curup Islamic Junior High School (SMPIT). This study used a qualitative approach, with data sources for the principal, Ustaz and ustazah, and students. Data collection using unstructured interviews. The validity of the data obtained was checked using triangulation of sources, then analyzed using the Miles and Huberman model. The results showed that several types of worship that were accustomed to students were congregational prayer, rawatib circumcision prayer, duha prayer, tahajud prayer, tahsin, tahfiz, and circumcision fasting Monday Thursday and fasting circumcision on Arafah day. The pattern of refraction is carried out in three stages, knowing, feeling, and doing. Operant conditioning theory applied to familiarize students is to provide reward and punishment and give examples and do mentoring activities.